Manufacturing of Large‐Scale Titanium‐Based Porous Transport Layers for Polymer Electrolyte Membrane Electrolysis by Tape Casting. Issue 6 (15th February 2019) - Hackemüller, Franz Josef; Borgardt, Elena; Panchenko, Olha; Müller, Martin; Bram, Martin
Abstract : Polymer electrolyte membrane (PEM) electrolysis is an ideal method for the direct conversion of regenerative energy into hydrogen. A key component of PEM electrolysis stacks is the porous transport layer (PTL), which is usually comprised of titanium to withstand the harsh conditions of water splitting. This present study investigates the potential of tape casting as a means of mass producing titanium transport layers in a cost‐effective way. Gas‐atomized and hydrogenation–dehydrogenation titanium powders are used as starting materials. A systematic study is conducted to find processing parameters, which can demonstrate the potential of tape casting as a means of manufacturing large‐scale porous transport layers for PEM electrolyzers. For proof of concept, the dimensions of the porous transport layer are scaled up to 470 × 470 mm 2 (at a thickness of 300 μm) and the component is successfully operated in an industrial electrolyzer under realistic conditions. Abstract : Tape casting titanium powders is a promising method of producing large‐scale porous transport layers for polymer electrolyte membrane (PEM) electrolysis cells. It is proven possible to manufacture tape‐cast transport layers of up to 470 × 470 mm 2 in size. The optimum process conditions are defined based on the systematic study of electrochemical and mechanical properties.